Self Disclosure SEVENTEEN CARAT Melalui Fan Account di Media Sosial Twitter “X” - Amanda Diva; Yudiana Indriastuti (Yayasan Perguruan Kampus, 2024)
The emergence of social media can be anytime and anywhere sharing anything about personal things, as well as feelings and activities in the media. Twitter social media